How Many Instruments Do We Really Need? A First-Best Optimal Solution to Multiple Objectives with Fisheries Regulation - Christian Elleby; Frank Jensen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
Part of the existing economic literature on fisheries regulation focuses on addressing several objectives with one instrument. In an extension of this literature we investigate the following three objectives of fisheries regulation: A) Correcting a stock externality; B) Raising public funds, and; C) Solving problems with uncertainty. We analyze the implications of combining a non-linear tax on harvest and individual transferable quotas to address these three objectives and argue that a tax alone can fulfill all three objectives simultaneously. This result can be related to the theory on a first-best and a second-best optimum which state that the number of objectives must be identical to the number of instruments if a first-best optimum shall be reached. We show that one instrument (a tax based on the size of the harvest in this case) is enough to achieve a first-best optimum.
Keywords: Q22; D80; H20; H23; 330; Stock externalities; double-dividend; uncertainty; taxes; quotas